Aggregation in Vitro of Immature Thrombocytes from Early Chick Embryos - Greenberg, Judith H (Thrombosis and Haemostasis, 1972)
Mammalian platelets and nonmammalian thrombocytes, although they perform a similar function, differ in morphology and in their response to thrombogenic agents. The present experiments extend the comparison between the two cell types to include the immature form of thrombocytes found in early chick embryos. Agents known to induce, or to inhibit, aggregation of platelets were tested for their effect on thrombocytes which were isolated from chick embryos of five days incubation age and which had been suspended in a tris-buffered saline solution containing EDTA. The degree of aggregation of thrombocytes was determined by phase microscopy after treatment with thrombin, trypsin, adenosine 5′-diphosphate (ADP), calcium chloride, or the sulfhydryl inhibitor N-ethylmaleimide. Approximately 450 trials were performed using 102 samples of blood, each sample being obtained by the pooling of the blood of five to six dozen embryos. The results demonstrate that thrombin and trypsin, in the presence of calcium ions, induce significant aggregation compared to that of untreated controls. Thrombin, in the absence of calcium ions, is ineffective in inducing aggregation, as is calcium chloride alone, or ADP in the presence or absence of calcium ions. Pretreatment of the thrombocytes with N-ethylmaleimide inhibited aggregation by thrombin in the presence of calcium chloride. It may be concluded that embryonic thrombocytes resemble platelets in their response to all the aggregating agents tested, with the exception of ADP, but resemble the thrombocytes of adult chickens in their failure to respond to ADP.